Synthesis, characterization and application of Ag doped ZnO nanoparticles in a composite resin - Dias, Hércules Bezerra [UNESP]; Bernardi, Maria Inês Basso; Marangoni, Valéria Spolon; de Abreu Bernardi, Adilson César; de Souza Rastelli, Alessandra Nara [UNESP]; Hernandes, Antônio Carlos (Elsevier, 2019)
The biofilm accumulation over the composite resin restorations can contribute to the formation of secondary caries. In this way, antibacterial restorative composite resins are highly desired. Then, the purpose of this study was to modify a composite resins using Ag doped ZnO nanoparticles (NPs), evaluate the antibacterial and mechanical properties of the modified composite resin. The ZnO/AgNPs were synthesized by two different routes, polymeric precursor and coprecipitation methods, and characterized by thermal decomposition, X-ray diffraction, specific surface area by N 2 desorption/desorption and scanning electron microscopy (SEM). Antibacterial activity of composite resin specimens (4 mm in height and 2 mm in diameter; n = 15) modified by ZnO/Ag nanoparticles was performed against 7-days Streptococcus mutans biofilm. Colony forming units (CFU/mL) were used to evaluate the bacterial activity. Additionally, the morphology and the bacteria adherence area were analyzed by SEM images. Cylindrical specimens (6 mm in height and 4 mm in diameter; n = 20) of the composite resin containing ZnO/Ag NPs were prepared to perform compressive strength in a universal mechanical test machine, and the surface of fractured specimens was analyzed by EDX element mapping to verify NPs homogeneity. The normal distribution was confirmed and the two-way analysis of variance (ANOVA) and Tukey's test for pair comparison were performed. The nanospheres of ZnO/Ag lead to a better biofilm inhibition, than nanoplates. No difference on compressive strength was found for the composite resin modified by ZnO/Ag nanoplates. Based on these results, this material could be a good option as a new restorative material.
Keywords: Antibacterial agent; Biofilms; Dental caries; Nanoparticles; Silver; Streptococcus mutans; Zinc oxide